The influence of perceived support and proactive personality in influencing entreprenurial intentions among working individuals in Malaysia - Ismail, Mohamed Yazid (2017)
This study aims to explore the existence of entrepreneurial intentions of wage or salaried individual in an emergent country, in which working adults in Malaysia is used as a test population. Samples taken in the test population were used to study and explore the relationship between proactive personalities and support (educational support & relational support) towards entrepreneurial intentions. The hypotheses of these variables against entrepreneurial intentions were tested on the sample population in order to develop an empirical model for entrepreneurial intentions for wage or salaried individuals in an emergent economy. A total a sample of 164 respondents who are working in Malaysia took part in this study by completing a questionnaire survey. The output of this survey was then further analysed using hierarchical multiple regression analysis, utilizing the SPSS software. Analyses of the result indicate that among the three variables, only proactive personality and educational support were able to influence the entrepreneurial intentions of wage or salaried individuals in Malaysia. It was also found that between the two variables, proactive personality was discovered to have a stronger influence towards entrepreneurial intent. This result is unique as the there have been limited study on entrepreneurial intentions among wage or salaried individuals particularly in Malaysia. The uniqueness of this study and its findings has potential to influence the development entrepreneurial education, policy and support for salaried individuals Malaysia to start a business. The recommendation towards policy makers, business community and individuals as result of these findings are further discussed in this paper.